Effect of disturbance on plant species abundance and density distribution in tropical forest of Sunsari district, Eastern Nepal - Gautam, Tilak Prasad; Mandal, Tej Narayan (Nepalese Journal of Biosciences, 2016)
The disappearance of global tropical forests due to deforestation and forest degradation has reduced the biodiversity and carbon sequestration capacity. In these contexts, present study was carried out to understand the species composition and density in the undisturbed and disturbed stands of moist tropical forest located in Sunsari district of eastern Nepal. Study revealed that the forest disturbance has reduced the number of tree species by 33% and tree density by 50%. In contrary, both number and density of herb and shrub species have increased with forest disturbance.